Development of recoverable magnetic mesoporous carbon adsorbent for removal of methyl blue and methyl orange from wastewater. Issue 5 (October 2020) - Azam, Kshaf; Raza, Rizwan; Shezad, Nasir; Shabir, Maira; Yang, Wenshu; Ahmad, Nabeel; Shafiq, Iqrash; Akhter, Parveen; Razzaq, Abdul; Hussain, Murid
Graphical abstract: Highlights: Activated carbon was synthesized from low cost rice husk by ZnCl2 activation. Mesoporous structure was given to activated carbon by synthesizing KIT-6 template. Iron nitrate (III) was used as a precursor for imparting magnetic behavior. The MMAC shows more adsorption for methyl blue and methyl orange dye than AC and MAC. The MMAC follows Langmuir isotherm for both methyl blue and methyl orange dye. Abstract: The novel magnetic mesoporous activated carbon (MMAC) was prepared from activated carbon (AC), produced from rice husk through ZnCl2 chemical activation. Meso-structure was induced via Korea Advanced Institute of Science and Technology-6 (KIT-6) silica formation and magnetic behavior was incorporated by magnetite by wetness impregnation method. KIT-6 silica enhances the porosity and provides a 3D structure to improve the adsorption process. The adsorption of methyl blue (MB) and methyl orange (MO) dyes on MMAC, mesoporous activated carbon (MAC) and AC was investigated and compared. The adsorbents were characterized by SEM, XRD, BET and FTIR analysis techniques. The effect of different process parameters on the adsorption efficiency such as pH of the dye solution, initial dye concentration and dosing of adsorbents were studied. The adsorption efficiency was evaluated by testing aliquot in UV–vis spectroscopy. The experimental data for the MMAC shows that MB followed the Freundlich isotherm while MO was well suited with the Langmuir model. The MMAC removed 82 % MB and 98.5 % MO dye solution in 30 min. The adsorbent was regenerated and reused for MB and MO for 4 cycles without a significant decrease in the adsorption efficiency. The MMAC was found to be the most efficient adsorbent than MAC and AC because of its high surface area and high pore volume. The magnetic behavior of MMAC separates the adsorbent after the adsorption process, making it potential adsorbent for water treatment.